2013
DOI: 10.1111/jog.12235
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of ovarian cancer with large cell neuroendocrine carcinoma: Case report and review of published works

Abstract: Large cell neuroendocrine carcinoma (LCNEC) is well-reported to result in unfavorable prognoses in many organ cancers while being rarely reported in gynecologic cancer, especially ovarian and endometrial cancers. Here we report a case of ovarian cancer with LCNEC which spread to distant organs within 1 year of primary surgery despite the fact that the post-surgical stage was Ia. The case received platinum-based chemotherapy as an adjuvant therapy after her curative surgery. However, LCNEC in the case was resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Inconsistent outcomes regarding the prognostic significance of NAC may be related to the failure to consider tumor grade, histotype, stage, and chemotherapy response [27–32]. In the current study, we identified optimal IDS and prognosis-related factors in advanced HG-EOC patients who underwent NAC.…”
Section: Discussionmentioning
confidence: 87%
“…Inconsistent outcomes regarding the prognostic significance of NAC may be related to the failure to consider tumor grade, histotype, stage, and chemotherapy response [27–32]. In the current study, we identified optimal IDS and prognosis-related factors in advanced HG-EOC patients who underwent NAC.…”
Section: Discussionmentioning
confidence: 87%
“…LCNEC is a type of neuroendocrine tumour that can affect lungs, gall bladder,7 urinary bladder,8 head and neck,9 prostate,10 ovary,11 uterine cervix,12 vagina,13 endometrium,14 breast,15 colon,16 ileum,17 rectum,18 bile ducts,19 stomach,20 renal pelvis,21 skin,22 thymus,23 etc. Pulmonary neuroendocrine tumours make up to 20% of all lung cancers of which LCNEC are 10% (ie, 2–3% of all lung cancers).…”
Section: Discussionmentioning
confidence: 99%
“…LCNEC is usually accompanied by other epithelial and germ tumor, pure LCNEC is extremely rare [5][6][7][8] . Despite extensive surgery and adjuvant chemotherapy performed for this type of tumor, the prognosis is common poor in the published literatures, even when diagnosis is made at an early stage [3,9,10] . Here, we present a case of a 37 year old woman who was diagnosed with stage IIIA1 LCNEC of the ovary.…”
Section: Introductionmentioning
confidence: 99%